Deforestation impacts of environmental services payments: Costa Rica's PSA Program 200-2005 - Environment for Development (2008)
Costa Rica’s environmental services payments program (Pagos por Servicios Ambientales, or PSA) started in 1997 and was the true pioneer in this area. It is broadly cited and has led to numerous calls for emulating its approach in various ways. It has itself evolved over time, with acknowledged shifts in focus. To measure the impacts of changed implementation, following earlier work on the 1997–2000 payments (Sánchez-Azofeifa et al. 2007; Pfaff et al. 2007), we evaluated the impact of the PSA forest protection contracts during 2000 and 2005. We found that less than 1 in 100 (about 0.4 percent) of the parcels enrolled in the program would have been deforested annually without payments, i.e., due to the net impact of the land returns in agriculture versus in ecotourism, as well as the effects of other conservation policies. This low return on investment is, to first order, the same as was seen for 1997–2000. However, we found that shifts in implementation have eliminated the bias in PSA location toward places where PSA’s impact on deforestation was even lower than on average plots. Thus, we showed that the impact increased due to changes in how program parcels were chosen. However, significant potential gains can be realized by increased targeting of areas with some deforestation pressure, including with payments that differ over space.